Sustainability in Food Production: A High-Efficiency Offshore Greenhouse - Francesco Barreca (Agronomy, 2024)
The world’s population is expected to increase by nearly two billion in the next 30 years; the population will increase from 8 billion to 9.7 billion by 2050 and could peak at 10.4 billion by the mid-2080s. The extreme weather triggered by global climate change has severely hit crop yields in open-field cultivation and led to an increase in food prices. Furthermore, in the last few years, emergency events such as the COVID-19 pandemic, wars/conflicts, and economic downturns have conditioned agricultural production and food security around the world. Greenhouses could be efficient cultivation systems because they enable food production in a sustainable way, limiting contact between pollutants and plants and optimizing the use of water, energy, and soil. This paper proposes a novel dome-soilless greenhouse concept for tomato cultivation in the Mediterranean area. The proposed greenhouse is fixed on a sea platform to take advantage of the seawater cooling environment and to integrate water consumption into a hydroponic system. In order to evaluate the best covering solution material to adopt, a few thermal and photometric characteristics of greenhouse covering materials were evaluated using a simplified method. A dynamic simulation was carried out to compare the proposed seawater cooling system with a conventional cooling tower in terms of the electric energy spent to maintain the inside temperature range at 13–25 °C across all seasons in the year. The proposed heating, ventilation, and air conditioning (HVAC) system allowed a total annual energy saving of more than 10%. The energy saved was a result of the better cooling performance of the seawater heat exchange that allowed energy saving of about 14% on cooling. The comparison between the model characterised by a 6 mm polycarbonate coupled with UbiGro film and a seawater cooling system, and the model including a 6 mm polycarbonate coupled with a clarix blue film covering and a tower cooling system highlighted energy saving of about 20%. The obtained results indicate possible future directions for offshore greenhouses to carry out independent production together with the integration of photovoltaic modules, water treatment plants, and smart remote-control systems.